2006
DOI: 10.1088/0957-4484/17/22/004
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetic anisotropy in ferrihydrite nanoparticles synthesized from reverse micelles

Abstract: Six-line ferrihydrite(FH) nanoparticles have been synthesized in the core of reverse micelles, used as nanoreactors to obtain average particle sizes < d > ≈ 2 to 4 nm. The blocking temperatures T m B extracted from magnetization data increased from ≈ 10 to 20 K for increasing particle size. Lowtemperature Mössbauer measurements allowed to observe the onset of differentiated contributions from particle core and surface as the particle size increases. The magnetic properties measured in the liquid state of the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 31 publications
6
17
0
1
Order By: Relevance
“…Taken in combination with the observation that at 30 Konly adoublet species exists, this value points to core particles with sizes below 2.4 nm. [23][24][25] This is also in agreement with the amount of iron, 24 and 96 57 Fe II /Dps,w hich using as tructural model for ferrihydrite gives an estimation for core particle sizes with less than 2.2 nm. [26] However,for these small iron loads,particle density and spatial distribution on the inner cavity surface should be considered.…”
supporting
confidence: 81%
“…Taken in combination with the observation that at 30 Konly adoublet species exists, this value points to core particles with sizes below 2.4 nm. [23][24][25] This is also in agreement with the amount of iron, 24 and 96 57 Fe II /Dps,w hich using as tructural model for ferrihydrite gives an estimation for core particle sizes with less than 2.2 nm. [26] However,for these small iron loads,particle density and spatial distribution on the inner cavity surface should be considered.…”
supporting
confidence: 81%
“…Xiong et al [38] confirmed that 2-line ferrihydrite (Fe 5 HO 8 ·4H 2 O) was the only mineral phase that was present during the hydrolysis of ferric ions at pH ∼8 with a considerable amount of sulfates in the solution system. However, 2-line ferrihydrite is a poorly crystallized ferric hydroxide with two weak broad XRD peaks [39]. In the present study, poorly crystallized ferric hydroxide was indeed found in the SEM image of NSW (Fig.…”
Section: 4supporting
confidence: 70%
“…The blocking temperature signals the range for which the time scale of magnetization measurements equals the relaxation time, and thus the anisotropy constant can be estimated from the T B value of the ZFC curve: 27 where K eff is the effective anisotropy constant, V is the particle volume, k B is the Boltzmann's constant, τ is the superparamagnetic relaxation time, and τ 0 is a factor of the order of 10 -9-10 -12 . [28][29][30] From eq 1 and with use of the T B value from 4 results in large magnetization values originated in the uncompensation of the antiferromagnetic B sublattice, which is known to be fully populated in normal configuration.…”
Section: Structural Studies From the Tem Images Shown Inmentioning
confidence: 99%